S-link to giga bit ethernet adapter- new frame segmentation for LHCb data acquisition system - Neves, Joaquim José Santos Esteves (2003)
Data Acquisition and Control Systems used in high energy physics experiments, such as those which will take place in the Large Hadron Collider (LHC) at CERN, require the specification of data formats and transmission protocols as well as the use of high speed links and interfaces. In this context, a new Frame Segmentation process will be presented and discussed, based on data formats adopted by the LHCb experience for the interconnection of two standardized systems: S-link and Gigabit Ethernet. Simulation results of the transfer capacity of the proposed mechanism will be also reported, together with guidelines for its physical implementation.